The antioxidant system of seminal fluid during in vitro storage of sterlet Acipenser ruthenus sperm - Dzyuba, Viktoriya; Cosson, Jacky; Dzyuba, Borys; Yamaner, Gunes; Rodina, Marek; Linhart, Otomar (Fish physiology and biochemistry, 2016)
The role of the seminal fluid antioxidant system in protection against damage to spermatozoa during in vitro sperm storage is unclear. This study investigated the effect of in vitro storage of sterlet Acipenser ruthenus spermatozoa together with seminal fluid for 36 h at 4 °C on spermatozoon motility rate and curvilinear velocity, thiobarbituric acid reactive substance level, and components of enzyme and non-enzyme antioxidant system (superoxide dismutase and catalase activity and uric acid concentration) in seminal fluid. Spermatozoon motility parameters after sperm storage were significantly decreased, while the level of thiobarbituric acid reactive substances, activity of superoxide dismutase and catalase, and uric acid concentration did not change. Our findings suggest that the antioxidant system of sterlet seminal fluid is effective in preventing oxidative stress during short-term sperm storage and prompt future investigations of changes in spermatozoon homeostasis and in spermatozoon plasma membrane structure which are other possible reasons of spermatozoon motility deterioration upon sperm storage.
Keywords: oxidační stres; Male; kyselina močová; Sperm Motility; Seminal fluid; látky reagující s kyselinou thiobarbiturovou; Antioxidant system; Spermatozoa; Thiobarbituric Acid Reactive Substances; mužské pohlaví; Uric Acid; ryby; Catalase; Fishes; sperma; Semen; Animals; Motility; zvířata; motilita spermií; katalasa; In vitro storage; Sterlet sperm; spermie; Superoxide Dismutase; Oxidative Stress; superoxiddismutasa